La presse jeune-turque en Égypte et la modernité (1895-1908) - Wajda Sendesni (Yod, 2012)
Egypt in the late nineteenth century became an important center of development of the press. Syrians and Turks fleeing the Hamidian repressive regime take refuge there. They publish newspapers in Cairo in Arabic, Turkish or bilingual where they criticize the sultan Abdulhamid and his regime and demand the restoration of the Ottoman constitution suspended in 1877. But in these papers, one can also detect an interest in modernity and progress that appears throw articles on modernity, progress, science, education, literature, etc. For the young Ottoman elite, rather than regime change, the future of the empire depends on its ability to transform and modernize because only modernity can save it from collapse by providing a social and economic reform.